-28-7=10x+23

Simple and best practice solution for -28-7=10x+23 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -28-7=10x+23 equation:


Simplifying
-28 + -7 = 10x + 23

Combine like terms: -28 + -7 = -35
-35 = 10x + 23

Reorder the terms:
-35 = 23 + 10x

Solving
-35 = 23 + 10x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-10x' to each side of the equation.
-35 + -10x = 23 + 10x + -10x

Combine like terms: 10x + -10x = 0
-35 + -10x = 23 + 0
-35 + -10x = 23

Add '35' to each side of the equation.
-35 + 35 + -10x = 23 + 35

Combine like terms: -35 + 35 = 0
0 + -10x = 23 + 35
-10x = 23 + 35

Combine like terms: 23 + 35 = 58
-10x = 58

Divide each side by '-10'.
x = -5.8

Simplifying
x = -5.8

See similar equations:

| x^6=1.4 | | 2+(x-3)+1=7 | | 35=7d | | 11-t=21 | | 40x^2+20x=0 | | 11=m+6 | | 125=20y-5(15-y) | | 370=m-72 | | c+c+2+c+4+c+6=(c+c+2)+10 | | 13x-131=4x-14 | | 359=n+116 | | 2c+12=12 | | 9y-65=2y+9 | | 6-7x=40-21x | | b+19=993 | | c-10=2 | | X^2x+1=0 | | 56=4b | | 9x-29=3x+21 | | p-26=6 | | 3y-10=2y-3 | | b+53=72 | | 15=f-25 | | 2x=9.555 | | c-2=47 | | j+181=-360 | | 65=p-21 | | 5T=T+1900+(T+1900)-1500 | | 13ab=7-28ab | | 45=z+29 | | 15x=30-10x | | 45 = z+ 29 |

Equations solver categories